Understanding the potential for selective natural organic matter removal by ion exchange - Finkbeiner, Pascal; Redman, J.; Patriarca, V.; Moore, Graeme; Jefferson, Bruce; Jarvis, Peter (Elsevier, 2018)
Dissolved organic carbon (DOC) removal from a river water source was investigated using ion exchange (IEX), coagulation and membrane filtration. This research linked the variable charge characteristics of the organic compounds present in the source water with removal by IEX and coagulation. The raw water charge density fluctuated considerably (between 5.4 and 10.7 meq mgDOC−1) and controlled removal of the charge loading. Importantly, charge density was not correlated with the organic carbon concentration. The combined IEX and coagulation process reduced the specific DBP-FP (sDBP-FP) of the final water, with values as low as 18 μg mgDOC−1 for both haloacetic acids and trihalomethanes. IEX removed a particular fraction of NOM that 1) enhanced coagulation efficiency, providing increased removal of overall DOC; and 2) enabled coagulation to subsequently remove higher levels of specific components of NOM that have a high DBP-FP. The component of NOM removed by IEX that had a positive impact on coagulation was identified to be charged low molecular weight organic compounds of all hydrophobicity levels, resulting in a reduced specific DBP-FP compared to coagulation alone.
Keywords: Ion-exchange; Organic carbon; Disinfection by-products; Coagulation; Natural organic matter